Search for the Standard Model Higgs boson in the $H →$ WW(*) $→ \ell ν \ell ν$ decay mode with 4.7 /fb of ATLAS data at $\sqrt{s}=7$ TeV - ATLAS collaboration (2864 authors) (2013)
A search for the Standard Model Higgs boson in the H -> WW(*) -> l nu l nu (l = e, mu) decay mode is presented. The search is performed using proton-proton collision data corresponding to an integrated luminosity of 4.7 /fb at a centre-of-mass energy of 7 TeV collected during 2011 with the ATLAS detector at the Large Hadron Collider. No significant excess of events over the expected background is observed. An upper bound is placed on the Higgs boson production cross section as a function of its mass. A Standard Model Higgs boson with mass in the range between 133 GeV and 261 GeV is excluded at 95% confidence level, while the expected exclusion range is from 127 GeV to 233 GeV.